Three concepts of tolerance - Thacker, Justin (European journal of theology, 2015)
This article begins by briefly discussing two well-described concepts of tolerance, and offering some acknowledged critiques of both. It then highlights Jesus' counter-cultural practice of table-fellowship and draws on this to provide a third model of tolerance, based around the art and science of conversation. It suggests that the contemporary dinner party provides a concrete example of this tolerance which, with appropriate modifications, could be scalable to provide a paradigm for tolerance at the macro, public level of discourse.